2019
DOI: 10.1016/j.psyneuen.2018.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Limbic response to stress linking life trauma and hypothalamus-pituitary-adrenal axis function

Abstract: Trauma alters neuroendocrine responses to stress and increases vulnerability to stress-related disorders. Yet, relationships among trauma, stress-induced neural changes and hypothalamic-pituitary-adrenal (HPA) axis activity have not been determined. The present study used functional magnetic resonance imaging to investigate the impact of life trauma on basal cortisol levels and neural responses to acute stress in 73 healthy individuals during brief stress and neutral-relaxing imagery using a well-established, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 47 publications
0
19
1
Order By: Relevance
“…ELS also results in long-lasting neural alterations in CRF brain systems that underlie the stress response and bidirectionally interact with the HPA axis. A recent study investigating the relationship between lifetime trauma exposure, HPA axis activity, and neural responses to acute stress in healthy adults found that greater trauma was associated with lower morning cortisol levels, and that greater trauma and lower cortisol are related to increased amygdala and hippocampal responses to stress (Seo, Rabinowitz, Douglas, & Sinha, 2019). The study reported that increased amygdala and hippocampal neural activity mediated the relationship between life trauma and decreased cortisol levels, suggesting that the effects of trauma on HPA activity may occur indirectly through a sensitized stress response in the limbic regions involved in positive and negative feedback of the HPA axis.…”
Section: Hpa Axis and Crf Brain Systemsmentioning
confidence: 99%
“…ELS also results in long-lasting neural alterations in CRF brain systems that underlie the stress response and bidirectionally interact with the HPA axis. A recent study investigating the relationship between lifetime trauma exposure, HPA axis activity, and neural responses to acute stress in healthy adults found that greater trauma was associated with lower morning cortisol levels, and that greater trauma and lower cortisol are related to increased amygdala and hippocampal responses to stress (Seo, Rabinowitz, Douglas, & Sinha, 2019). The study reported that increased amygdala and hippocampal neural activity mediated the relationship between life trauma and decreased cortisol levels, suggesting that the effects of trauma on HPA activity may occur indirectly through a sensitized stress response in the limbic regions involved in positive and negative feedback of the HPA axis.…”
Section: Hpa Axis and Crf Brain Systemsmentioning
confidence: 99%
“…While it was originally assumed that high cortisol causes the hippocampal volume reduction, newer studies discuss the hippocampus as an important mediator in stress reactivity. Accordingly, participants with smaller hippocampi show reduced cortisol awakening response ( Valli et al, 2016 ; Seo et al, 2019 ; Pruessner et al, 2007 ; Dedovic et al, 2010 ; Buchanan et al, 2004 ) and reduced stress reactivity of the HPA-axis ( Frodl et al, 2014 ; Valli et al, 2016 ; Pruessner et al, 2007 ; Knoops et al, 2010 ). Likewise, hippocampal damage abolishes the cortisol response to psychosocial stress ( Buchanan et al, 2009 ).…”
Section: Neuroimaging Studies On the Effects Of Sex And Stress Hormonmentioning
confidence: 99%
“…As the TSST requires speaking and alteration of experimental scenes, which causes head movement and hence is not optimal for functional imaging (Ming et al, 2017), no study has investigated responses under psychosocial stress in adults with histories of childhood maltreatment using such modalities. Other studies induced stress by a script which based on autobiographical memory (Seo et al, 2019;Zhai et al, 2019), which may have inherent limitations (Britton et al, 2005). In addition, the majority of studies describing maltreatmentrelated changes have been conducted with subjects already affected by major depressive disorder, anxiety, or posttraumatic stress disorder.…”
Section: Introductionmentioning
confidence: 99%